Factors affecting intention to purchase edible bird’s nest products: the case of Malaysian consumers - Sharifuddin, Juwaidah; Ramalingam, Leelanayagi; Mohamed, Zainal Abidin; Rezai, Golnaz (Routledge, 2014)
Malaysia is the second largest producer of edible bird’s nest (EBN) in the world, but it has encountered problems when its main export market, China, imposed a ban on EBN products originating from the country. Edible bird’s nest products are products made of the hardened saliva secretions of swiftlet birds. Purchasing intention of edible bird’s nest products is a vital variable in determining customers’ purchasing behavior for these products. This research explores how attitude, subjective norms, and perceived behavioral control can influence the buyer’s intention toward purchasing edible bird’s nest products. A total of 1,361 respondents were interviewed using a structured questionnaire from July to November 2012. Descriptive analysis, factor analysis, and multiple regression were used to analyze the data. Multiple regression analysis shows that attitude, subjective norms, and perceived behavioral control are statistically significant predictors of consumer intention toward purchasing edible bird’s nest products.